The Freelance Consultant - Newton, Richard (FT Publishing International, 2021)
Freelance consulting, coaching, IT contracting and other self-employed professional roles are fast becoming the preferred way to find fulfilling work, generate a great income, and futureproof careers, whilst giving all the benefits and freedoms of being your own boss - but few know how to make it really work. The Freelance Consultant is the comprehensive guide into turning your expertise into a viable, and valuable, business. With independent consultant Richard Newton, you will discover a wealth of insider knowledge as well as a network of other successful advisors willing to share their stories. The Freelance Consultant will explain how to: Setup, run and thrive in your freelance, consultant or coaching business. Acquire those vital first paying clients. Know what it takes to become a successful, dierentiated and valuable advisor. Build your business, dene your services and set your prices. Understand your customers and identify, manage, and retain key clients. Keep developing and continually improving your skills an growing your business. Turn from amateur to pro with the help of The Freelance Consultant.